Female Business Ownership and Informal Sector Persistence - Ghani, Ejaz; Kerr, William R.; O'Connell, Stephen D. (World Bank, Washington, DC, 2014)
The informal sector in India has been exceptionally persistent over the past two decades. Is this a bad thing? Not necessarily. This paper shows that a substantial share of the persistence in India's unorganized manufacturing sector is due to the rapid increase in female-owned businesses. Had women's participation remained in the proportion to male-owned businesses that was evident in 1994, the unorganized manufacturing sector would have declined in share rather than increased. Most of these new female-owned businesses are opened in the household and at a small scale, about a third of the size of a typical male-owned business in the informal sector. Yet, it appears that these businesses offer economic opportunities not otherwise present and a transition for some women from unpaid domestic work.